2021
DOI: 10.1002/etc.5035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyester Microplastic Fiber Contamination on Amphibian–Trematode Interactions

Abstract: Microplastic contamination poses a global threat to aquatic organisms, yet we know little as to how microplastics may indirectly affect organismal health via their influence on species–species interactions (e.g., host–parasite interactions). This is problematic because microplastic‐mediated alterations to host–parasite dynamics could negatively impact individual‐ population‐level health of hosts. Using a larval amphibian (host) and free‐living trematode (parasite) model, we asked whether 1) polyester microplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Overall, the authors concluded that we should treat microplastics as a multiple stressor with both physical and chemical stressors rather than a single contaminant. The complex interactions between microplastics and biota were further observed by Buss et al (2022), who observed that polyester microplastic fibers can augment host-parasite interactions at high concentrations in amphibians. Stankovic´et al (2022) observed negligible effects of microplastics on community structure in benthic macroinvertebrates but do postulate that long-term presence of microplastics in the sediment may lead to significant changes in community structure driven by sublethal effects.…”
Section: Relevant and Realistic Assessments Of Micro-and Nanoplastics...mentioning
confidence: 81%
“…Overall, the authors concluded that we should treat microplastics as a multiple stressor with both physical and chemical stressors rather than a single contaminant. The complex interactions between microplastics and biota were further observed by Buss et al (2022), who observed that polyester microplastic fibers can augment host-parasite interactions at high concentrations in amphibians. Stankovic´et al (2022) observed negligible effects of microplastics on community structure in benthic macroinvertebrates but do postulate that long-term presence of microplastics in the sediment may lead to significant changes in community structure driven by sublethal effects.…”
Section: Relevant and Realistic Assessments Of Micro-and Nanoplastics...mentioning
confidence: 81%
“…For instance, exposure to microplastics or NPs can cause behavioural changes affecting the outcome of predator-prey interactions (de Sá et al, 2015;Mattsson et al, 2017;Seuront, 2018). Recent evidence suggests that host-parasite interactions can also be affected: a parasitic chytrid fungus displayed lower success infecting their phytoplankton hosts when exposed to NPs (Schampera et al, 2021), and similar results were found for trematodes infecting amphibians, when exposed to microplastics (Buss et al, 2021). Thus, it seems that microplastics and NPs have the potential to modulate biotic interactions in aquatic systems, a perspective that has been largely overlooked so far, but requires further attention.…”
Section: Most Studies Have Investigated the Effects Of Microplastics Andmentioning
confidence: 83%
“…Two concentrations of NPs were prepared in the SSS‐medium as NP exposure treatments: 5 mg/L (i.e., low‐NP) and 20 mg/L (i.e., high‐NP). These concentrations have been commonly applied in Daphnia studies investigating the toxicity of polystyrene NPs (e.g., Cui et al, 2017; Lin et al, 2019; Pochelon et al, 2021), as well as recent experiments using microplastics or NPs on freshwater host–parasite systems (Buss et al, 2021; Schampera et al, 2021). The zero‐NP treatment was prepared without any addition of NPs.…”
Section: Methodsmentioning
confidence: 99%
“…16) In fact, MPs concentrations of 30.7 × 10 3 particles (kg dry sludge) -1 has been reported. 17) A large amount of plastic mulch is used in agricultural fields, so the concentrations of MPs in soil may also increase. 18) The size of MPs is one of the important factors that contribute to the effects of MPs.…”
Section: Effect Of Mps On Soil Propertiesmentioning
confidence: 99%